The Role of The Special Development Institution For Children (LPKA) As A Rehabilitation Center For Juvenile Offenders - Fajar Sitorus; Janpatar Simamora (International Journal of Law and Society, 2025)
In Indonesia's correctional system, correctional institutions play a vital role, particularly in educating offenders, including juvenile offenders. Juvenile offenders are individuals under 17 years of age or those who do not yet possess an ID card, commonly referred to as children. Since children are in their developmental stage and are vulnerable to environmental influences that may worsen their psychosocial condition, rehabilitation often poses significant challenges for them. Therefore, correctional institutions are responsible for providing training that encompasses rehabilitation, social reintegration, and punishment. In this context, the rehabilitation process aims to fulfill the rights of children in correctional facilities, including access to formal and non-formal education, life skills training, and psychological counseling. The objective of this training is to equip children with the necessary skills to reintegrate into society after serving their sentence. Moreover, correctional institutions also play a role in fostering a sense of responsibility and self-esteem in juvenile offenders, enabling them to become active and positive members of society. The purpose of this study is to examine how correctional institutions contribute to the rehabilitation of juvenile offenders and the challenges faced in implementing rehabilitation programs that align with children's rights. The research findings reveal that, despite efforts by correctional institutions to implement various rehabilitation programs, such as education, skills training, and psychological counseling, there is still much to be improved.